2010
DOI: 10.1016/j.ntt.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid: Neurobehavioral consequences of exposure to a prevalent marine biotoxin

Abstract: Domoic acid (DA), the cause of Amnesic Shellfish Poisoning, is a naturally occurring marine biotoxin that is usually produced by the microscopic algae Pseudo-nitzschia. As is the case for other types of toxic algae, Pseudo-nitzschia outbreaks are becoming more frequent. Acute high-dose symptomology in humans includes vomiting, cramping, coma and death as well as neurological effects such as hallucinations, confusion and memory loss. Experimental studies and medical reports have collectively shown that DA expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…In humans, the hallmark of DomA-induced neurotoxicity is the rather dramatic disruption of memory processing. Clinical evaluation of 14 adult human subjects poisoned by DomA (after the outbreak in Canada) revealed that the majority of them (12/14) had severe antegrade memory deficits with relative preservation of higher cortical functions, since the patients were unable to remember events that occurred after DomA intoxication and had difficulty recalling new information (reviewed in Grant et al, 2010).…”
Section: Weight Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the hallmark of DomA-induced neurotoxicity is the rather dramatic disruption of memory processing. Clinical evaluation of 14 adult human subjects poisoned by DomA (after the outbreak in Canada) revealed that the majority of them (12/14) had severe antegrade memory deficits with relative preservation of higher cortical functions, since the patients were unable to remember events that occurred after DomA intoxication and had difficulty recalling new information (reviewed in Grant et al, 2010).…”
Section: Weight Of Evidencementioning
confidence: 99%
“…In a separate clinical report of one case, a patient that received treatment at the hospital for DomA poisoning showed memory impairment which was resolved after three weeks (reviewed in Grant et al, 2010). Other symptoms of the syndrome include nausea, vomiting, abdominal cramps, diarrhoea, headache, unstable blood pressure, cardiac arrhythmias and neurological dysfunction, including coma and seizures (reviewed in Grant et al, 2010).…”
Section: Weight Of Evidencementioning
confidence: 99%
“…In addition to the DSP-causing toxins, domoic acid (DA) -the main toxin which causes ASP outbreaks, produced by several species of the diatom Pseudo-nitzschia (JEFFERY et al, 2004;GRANT et al, 2010) -has also been recorded in South Brazil (PROENÇA;MAFRA Jr., 2005). Domoic acid, which is responsible for massive mortalities of birds and marine mammals following the ingestion of contaminated fish (BELTRÀN et al, 1997;LEFEBVRE et al, 1999), can also intoxicate humans through the consumption of bivalve mollusks that accumulate the toxin in their tissues, mainly in the hepatopancreas and viscera (PERL et al, 1990;GRANT et al, 2010;MAFRA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Domoic acid, which is responsible for massive mortalities of birds and marine mammals following the ingestion of contaminated fish (BELTRÀN et al, 1997;LEFEBVRE et al, 1999), can also intoxicate humans through the consumption of bivalve mollusks that accumulate the toxin in their tissues, mainly in the hepatopancreas and viscera (PERL et al, 1990;GRANT et al, 2010;MAFRA et al, 2010). Although, only in special episodes, when a large number of Pseudo-nitzschia spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation